A preliminary investigation on the gastrointestinal helminths of the Barbados green monkey, Cercopithecus aethiops sabaeus - Alex Mutani; Kamara Rhynd; Gabriel Brown (Revista do Instituto de Medicina Tropical de São Paulo, 2003)
Faecal samples were collected from fifty three freshly captured monkeys which were kept at the Barbados Primate Research Centre and Wildlife Reserve (BPRCWR). Examination of these samples for gastrointestinal helminths using the zinc sulphate floatation method revealed an overall infection rate of 88.7%.The parasites observed included Strongyloides (62.4%), Physaloptera (58.5%), Trichuris (52.8%), Hookworm (34.0%), Oesophagostomum (30.2%), Trichostrongylus (3.8%) and Ascaris (5.7%). No significant differences in overall prevalence were observed according to sex or age. Polyparasitism appeared to be common as it was observed in 92.5% of all monkeys examined. It is concluded that these monkeys could act as reservoirs of some of the parasites which can infect man.